Petrophysical Analysis of Well Logs for Asmari Reservoir in Abu Ghirab Oil Field, South Eastern Iraq - Al-Baldawi, Buraq Adnan (Iraqi Journal of Science, 2020)
The present study includes the evaluation of petrophysical properties and lithological examination in two wells of Asmari Formation in Abu Ghirab oil field (AG-32 and AG-36), Missan governorate, southeastern Iraq. The petrophysical assessment was performed utilizing well logs information to characterize Asmari Formation. The well logs available, such as sonic, density, neutron, gamma ray, SP, and resistivity logs, were converted into computerized data using Neuralog programming. Using Interactive petrophysics software, the environmental corrections and reservoir parameters such as porosity, water saturation, hydrocarbon saturation, volume of bulk water, etc. were analyzed and interpreted. Lithological, mineralogical, and matrix recognition studies were performed using porosity combination cross plots. Petrophysical characteristics were determined and plotted as computer processing interpretation (CPI) using Interactive Petrophysics program. Based on petrophysical properties, Asmari Reservoir in Abu Ghirab oil field is classified into three sub formations: Jeribe/ Euphrates and Kirkuk group which is divided into two zones: upper Kirkuk zone, and Middle-Lower Kirkuk zone. Interpretation of well logs of Asmari Formation indicated a commercial Asmari Formation production with medium oil evidence in some ranges of the formation, especially in the upper Kirkuk zone at well X-1. However, well X-2, especially in the lower part of Jeribe/ Euphrates and Middle-Lower Kirkuk zone indicated low to medium oil evidence. Lithology of Asmari Formation demonstrated a range from massive dolomite in Jeribe/ Euphrates zone to limestone in upper Kirkuk zone and limestone and sandstone in middle-lower Kirkuk zone, whereas mineralogy of the reservoir showed calcite and dolomite with few amounts of anhydrite.